Hotspots and status of Fetal Alpha-Thalassemia from 2009 to 2023: a bibliometric analysis - Li, Qiuying; Li, Xinyan; He, Sheng; Li, Jiao (Frontiers in Pediatrics, 2024)
Objective to evaluate the research status and development hotspots of fetal α-thalassemia by quantitatively analyzing the diagnostic status, key areas, related management measures and prospects of the disease by bibliometrics. Methods The global literature on fetal α-thalassemia and severe α-thalassemia from 2009–2023 in the Web of Science Core Collection (WOSCC) was visually analyzed by VOSviewer and CiteSpace. Results (1) The examination of the quantity of publications concerning fetal α-thalassemia indicates a rising tendency prior to 2018, followed by a decrease after 2018. (2)The United States, China, Italy, Thailand have published more papers, and the United States has more collaborating countries such as Italy and China. (3) Chiang Mai University and Harvard University are the top two institutions with the highest contribution. However, Chiang Mai University's H index (12) and citation frequency per article (8.05) are relatively low and the NC (6,342), H index (33) and citations per article (75.42) of Harvard University are higher than those of the other institutions. (4) Tongsong T, Gambari R and Fucharoen S are the top three prolific authors. Fucharoen S emerges as the most frequently cited author with 738 citations, excluding self-citations. (5) HEMOGLOBIN leading with 87 published papers (NC:601,IF: 0.82, H-index: 13), followed by BLOOD(58 papers, Nc: 3755, IF: 25.48, H-index: 40) and BLOOD CELLS MOLECULES AND DISEASES(39 papers, Nc: 729, IF: 2.37, H-index: 16). (6) The most cited article was published in science and the second and third cited articles were featured in the Proceedings of the National Academy of Sciences; the top 3 clusters of co-cited literature are “gene editing”, “polymorphisms”, “hydroxyurea”. (7) Keywords analysis showe that the top two categories of keyword cluster focus on the prenatal diagnosis and the current treatment strategy of the disease, which remain the research hotspots. Conclusions Recent research on this topic has primarily focused on prenatal diagnosis and treatment strategies. A particular area of interest is the ongoing research on gene therapy.The advances in non-invasive diagnosis and therapeutic methods will change the current management approaches for fetal severe α-thalassemia in the future.